C9ORF72 knockdown triggers FTD-like symptoms and cell pathology in mice - Lopez-Herdoiza, Maria-Belen; Bauché, Stephanie; Wilmet, Baptiste; Le Duigou, Caroline; Roussel, Delphine; Frah, Magali; Béal, Jonas; Devely, Gabin; Boluda, Susana; Frick, Petra; Bouteiller, Delphine; Dussaud, Sébastien; et al. (Frontiers in Cellular Neuroscience, 2023)
The GGGGCC intronic repeat expansion within C9ORF72 is the most common genetic cause of ALS and FTD. This mutation results in toxic gain of function through accumulation of expanded RNA foci and aggregation of abnormally translated dipeptide repeat proteins, as well as loss of function due to impaired transcription of C9ORF72. A number of in vivo and in vitro models of gain and loss of function effects have suggested that both mechanisms synergize to cause the disease. However, the contribution of the loss of function mechanism remains poorly understood. We have generated C9ORF72 knockdown mice to mimic C9-FTD/ALS patients haploinsufficiency and investigate the role of this loss of function in the pathogenesis. We found that decreasing C9ORF72 leads to anomalies of the autophagy/lysosomal pathway, cytoplasmic accumulation of TDP-43 and decreased synaptic density in the cortex. Knockdown mice also developed FTD-like behavioural deficits and mild motor phenotypes at a later stage. These findings show that C9ORF72 partial loss of function contributes to the damaging events leading to C9-FTD/ALS.